PROPOSAL FOR RESEARCH AND DEVELOPMENT OF VERTEBRAL EXOSKELETON TO REDUCE PHYSICAL STRESS IN THE SPINE - Gabriel Quirino De Lima, João; Ferreira De Oliveira, Igor; Monaliza Cunha de Sousa, Aêda (Journal of Interdisciplinary Debates, 2022)
He presents work aims to develop a mechanism capable of assisting the physical efforts of the spine. Exoskeletons are currently tools developed by the field of engineering with important work in the medical physiotherapeutic area and in the search for a better performance of the human capacity to lift loads, being that the main focus of the use of such tools in the movement more quickly and efficient. The device in development is composed of low weight and flexible cylindrical structures connected by means of the fastening brackets which provide a modular characteristic to the system. Such a feature allows the exoskeleton to be adapted to aid movement. The performance of the exoskeleton is also modular, and can be performed passively, by means of springs and shock absorbers, or actively through actuators or motors.